Nutritional Status and Physical Development of High-Performance Combat Athletes in Lithuania - Marius Baranauskas; Linas Tubelis; Rimantas Stukas; Edmundas Švedas; Laimutė Samsonienė; Diana Karanauskienė (Lithuanian Sports University, 2018)
Background. Adequate nutrition is inseparable from athletes' optimal physical development and achieved sports performance.  Preparing  for  the  Olympic  Games  athletes'  nutrition  must  meet  certain  requirements.  Only  under appropriate nutrition conditions athletes are enabled to maximize their adaptation to physical loads.  Hypothesis: nutrition of Lithuanian high performance athletes in combat sports is adequate. Research aim was to assess nutrition profile and physical development of Lithuanian high performance athletes in combat sports. Methods.  During  the  competition  preparation  period  of  2012,  the  actual  diets  of  Lithuanian  elite  boxers (n = 14), and the Greco-Roman wrestlers (n = 29) were tested and evaluated. Body composition parameters and physical development of combat athletes were assessed using BIA tetra - polar electrode method. Athletes' actual diets were established using the actual dietary survey method. Results. Muscle and fat mass indexes of boxers and Greco-Roman wrestlers, 7.5 ± 3.8 and 5.4 ± 2.0 respectively, show that effective complex preparation measures ensure optimal body condition status of athletes. Nevertheless, the diets of combat sport athletes do not meet the requirements:  irrational use of proteins, not enough carbohydrates and polyunsaturated fatty acids, including omega-6 and omega-3 fatty acids, vitamins D, B 1 , PP, minerals, manganese, zinc, calcium and copper, too much intake of fat, saturated fatty acids and cholesterol.   Conclusion.  The  existing  diets  of  Lithuanian  elite  combat  sports  athletes  cannot  ensure  their  maximal adaptation to physical loads and must be optimized, individualized and adjusted, adding dietary supplements with extra carbohydrates, essential fatty acids, vitamins, minerals, and in exceptional cases, nutritional supplements with  essential amino acids. Keywords: high sports performance, combat sports, boxing, Greco-Roman wrestling, athlete nutrition, nutrition profle.